(untitled) (SAARC Journal of Agriculture, 2015)
As a very common feature of fish marketing, small-scale fisheries in tropical countries suffers from huge post-harvest loss every year. A method was proposed to quantify the post-harvest quality loss of wet fish using sensory based assessment tool. The assessments were conducted on four fish species (rohu Labeo rohita; Ilish Tenualosa ilisha, catfish Pangasius sutchi and tilapia Oreochromis niloticus) in different steps of major distribution channels in Bangladesh for a year. Sensory quality defect point data were standardized with corresponding biochemical and microbiological quality parameters through interval estimate based on regression analysis, where a near to actual sensory quality breaking point was found to be DP 3.3. High value of goodness of fit 2 R indicated a highly fitted regression model for all the fishes tested, with highly significant (p<0.01) estimated regression coefficients. Percent quality loss of fish at each step of distribution channel was determined using DP 3.3, constructing a (1-?) confidence interval for average percentage of defective fish. The loss assessment study indicated that fish did not lose quality during handling by the fishermen, and fish farmers or at landing centers and primary fish markets, except fresh T. ilisha destined for consumer market. While, T. ilisha used for salting during glut catch suffered substantial loss. Most of the quality losses were initiated at the transporters and commission agents, from 4% in P. sutchi to 11% in O. niloticus. When fish come to retailers, a 16% loss was recognized in L. rohita and O. niloticus, but 7% in P. sutchi and 9% in T. ilisha. Higher loss was observed in fish vendors, from 10% - 19%. Considering the retailers as the end-point stake in the fish distribution chain, study revealed the range of fish quality loss was 7-16% in four major consumed species in Bangladesh. The method was further validated in assessing the quality of 24 other major commercial fish species in different seasons and locations country-wide for two consecutive years and found identical results. The results suggest that the new method can be applied to any fish in quantifying the qualitative loss. SAARC J. Agri., 13(1): 75-89 (2015)